2018
DOI: 10.4103/ijri.ijri_128_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion tensor imaging in renal parenchymal changes

Abstract: Context:Diffusion Tensor Imaging (DTI) is a reliable noninvasive tool to assess renal function with medullary Fractional Anisotropy (FA) values showing the most consistent results.Aims:Evaluation of FA, Apparent Diffusion Coefficient (ADC) for detecting diabetic nephropathy (DN) using 1.5-Tesla magnetic resonance imaging (MRI). To determine FA and ADC values in chronic kidney disease (CKD) patients and controls, and comparing these with estimated glomerular filtiration rate (eGFR) and categorizing the stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Similarly, Saini et al . [ 29 ] in their study found an increasing trend in cortical FA values with increasing level of proteinuria and with reducing eGFR, but unlike our study, they did not find a significant difference in FA values between the microalbuminuric group and those with overt proteinuria. Conversely, in a study by Hueper et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Saini et al . [ 29 ] in their study found an increasing trend in cortical FA values with increasing level of proteinuria and with reducing eGFR, but unlike our study, they did not find a significant difference in FA values between the microalbuminuric group and those with overt proteinuria. Conversely, in a study by Hueper et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ], and Saini et al . [ 29 ]. The declining trend in the FA values in the medulla can be attributed to several models of histopathology that were observed previously: a) tubular atrophy and cellular damage influence the direction of diffusion, as suggested by the rat model [ 27 ]; b) collagen deposition and inflammatory cell infiltration also contribute; and c) disruption of normal glomerular filtration membrane structure results in filtering of macromolecular proteins and red blood cells into the tubules, which congest the tubules and impair radial diffusivity, resulting in reduced FA values in the medulla [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When histology is performed, FA was correlated with percent of glomerulosclerosis and the area of interstitial fibrosis as well as the degree of renal impairment (stages 1 to 5) (Feng et al, 2015). In CKD, a significant decline in medullary FA was reported in patients with chronic renal impairment (eGFR <60 mL/min/1.73 m 2 (Saini et al, 2018), renal failure caused by: nephroangiosclerosis, renal artery stenosis, medullary kidney cystic disease, DN, pyelonephritis, lithiasis, acute glomerulonephritis, analgesic abuse, interstitial nephritis, Wegener granulomatosis, LN, diuretic abuse (Gaudiano et al, 2013)) compared to control with normal renal function, and strongly correlated to eGFR (Gaudiano et al, 2013;Saini et al, 2018;. Tractography has also shown a good visual discrimination between the two subjects, where reduced number of tracts which do not have preferential orientation was presented with worsening renal function compared to a regular tracts arrangement with normal renal function (Gaudiano et al, 2013).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…Both organs are affected by similar vascular risk factors such as age, hypertension, diabetes mellitus and smoking [2]. Individuals with chronic kidney disease (CKD) present a plethora of small vessel disease related brain changes [1][2][3][4] with focal and diffuse structural and microstructural abnormalities [5][6][7]. These include lacunar strokes, white matter abnormalities and microbleeds [3,8,9].…”
Section: Introductionmentioning
confidence: 99%